1980
DOI: 10.1002/cne.901920307
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among lumbar motoneurons on opposite sides of the frog spinal cord: Morphological and electrophysiological studies

Abstract: Light and electron microscopy have been used to study the projections of dendrites from motoneurons in lumbar segments of the spinal cord of the frog following administration of horseradish peroxidase to cut ventral roots. Processes originating from motoneurons crossed to the opposite side of the spinal cord via the anterior commissure and made contact with dendrites and motoneuronal somata. Typically, in segments 6 to 8 the crossing dendrites showed irregular enlargements in diameter. Electrophysiological rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Since motoneurones in the spinal cord of the frog are electrically coupled (Erulkar & Soller, 1980;, it is important to distinguish sensory-motor synaptic potentials from 496 PROJECTIONS OF FOREIGN SENSORY NEURONES motoneurone coupling potentials. In normal animals only homonymous triceps motoneurones are coupled to each other and we also observed normal motoneuronal coupling after dorsal root section in the experimental animals.…”
Section: Methodsmentioning
confidence: 99%
“…Since motoneurones in the spinal cord of the frog are electrically coupled (Erulkar & Soller, 1980;, it is important to distinguish sensory-motor synaptic potentials from 496 PROJECTIONS OF FOREIGN SENSORY NEURONES motoneurone coupling potentials. In normal animals only homonymous triceps motoneurones are coupled to each other and we also observed normal motoneuronal coupling after dorsal root section in the experimental animals.…”
Section: Methodsmentioning
confidence: 99%
“…la, b). Only the medial motoneuron has dendrites which cross the midline [Grinnell, 1966;Stensaas and Stensaas, 1971;Erulkar and Soller, 1982], The medial motoneuron appears to have a greater dendritic range both rostrocaudally and mediolaterally.…”
Section: Resultsmentioning
confidence: 99%
“…Spinal motoneurons in frogs have been the subject of numerous physiological studies, particularly because of the separa tion of specific inputs onto their somata and their dendrites [Cruce, 1974], Many of these studies have concentrated on the re lationship between primary afferent fibers and dendrites of lateral motoneurons [Grantyn et al, 1982;Jhaveri and Frank, 1983;Lichtman et al, 1984], Lateral mo toneuron dendrites are of interest because they are contacted by primary afferent fib ers from spindles in limb musculature in nervated by the same motoneuron [Gran tyn et al, 1982;Jhaveri and Frank, 1983;Lichtman et al, 1984], Unlike lateral mo-toneurons, medial motoneurons innervate axial musculature and have dendrites which cross the midline [Grinnell, 1966;Erulkar and Soller, 1982], There is little quantitative information on motoneuron dendrite morphology such as length, surface area, volume, and peak branching. These data are useful in the analysis of synaptic input, since the re gion where dendrites are most highly branched may represent a site of abundant synaptic contacts.…”
Section: Introductionmentioning
confidence: 99%
“…The role of dendrodendritic interactions in the coactivation and synchronization of contra-and ipsilateral motoneurons was observed in various parts of the central nervous system [Grinnell, 1966;Stensaas and Stensaas, 1971;Erulkar and Soller, 1980;Bácskai et al, 2008;Campbell et al, 2009]. Our previous studies suggested a similar morphological organization of the XII motoneurons as their dendrites cross the midline and arborize within the confines of the contralateral XII nucleus [Matesz and Székely, 1977;Birinyi et al, 2004].…”
Section: Morphological Background Of XII Motor Activities During the mentioning
confidence: 91%